State-of-the-Art Impacts of Smart Grid in the Power Systems Operation and Expansion Planning - Oliveira,Gabriel Apoena de (2018)
ABSTRACT In this article, a state-of-the-art review on the impacts of Smart Grid in the operation and planning of the expansion of the Electric Power System is presented. The concept of Smart Grid is increasingly integrated in conventional networks, and the impact that this new technology generates on operation and planning must be investigated. Thus, in this article a survey of the main scientific publications was made with the purpose of determining the impacts and methodologies most used in this analysis. Efforts to analyze impacts are large because of the high degree of uncertainty of this new technology added to the problem. After the bibliographic survey, it was concluded that Robust Optimization and Genetic Algorithms are methodologies that are effective in problems of this nature and are the most adopted methods.